Population structure and genetic diversity of invasive Fall Armyworm after 2 years of introduction in India - N. Nayyar (Nature Portfolio, 2021)
Abstract Fall Armyworm (FAW), Spodoptera frugiperda, is a polyphagous pest capable of feeding over 80 plant species and was indigenous to the Western Hemisphere. Within a span of 4 years, FAW has established itself throughout most of the regions in Africa and Asia causing significant losses in maize production. Owing to its revamped distribution range, it would be prudent to analyze the ensuing genetic changes and study the emerging phylogeographic patterns across the world. In this regard, we would like to provide a current snapshot of genetic diversity of FAW in India 2 years after the initial introduction and compare it with the worldwide diversity in order to trace the origins and evolutionary trajectories of FAW in India. We have investigated around 190 FAW samples from different regions in India for strain identity and polymorphism analysis on the basis of partial mitochondrial cytochrome oxidase I (COI) gene sequences. Apart from the ancestral rice and corn strain haplotype, our study demonstrates the presence of 14 more haplotypes unique to India at a haplotype diversity of 0.356. We were also able to record inter-strain hybrid haplotypes of rice and corn strains in India. Regional heterogeneity within Indian populations seems to be quite low representative of extensive migration of FAW within India. Distribution analysis of pairwise differences and rejection of neutrality tests suggest that the FAW population in India might be undergoing expansion. Our data is consistent with the findings suggesting a recent and common origin for invasive FAW populations in Asia and Africa, and does not indicate multiple introductions to India. This study reports the highest genetic diversity for Indian FAW populations to date and will be useful to track the subsequent evolution of FAW in India. The findings would have important ramifications for FAW behavior and composition throughout the world.